5(c-7)-2(3x-4)=3x

Simple and best practice solution for 5(c-7)-2(3x-4)=3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(c-7)-2(3x-4)=3x equation:


Simplifying
5(c + -7) + -2(3x + -4) = 3x

Reorder the terms:
5(-7 + c) + -2(3x + -4) = 3x
(-7 * 5 + c * 5) + -2(3x + -4) = 3x
(-35 + 5c) + -2(3x + -4) = 3x

Reorder the terms:
-35 + 5c + -2(-4 + 3x) = 3x
-35 + 5c + (-4 * -2 + 3x * -2) = 3x
-35 + 5c + (8 + -6x) = 3x

Reorder the terms:
-35 + 8 + 5c + -6x = 3x

Combine like terms: -35 + 8 = -27
-27 + 5c + -6x = 3x

Solving
-27 + 5c + -6x = 3x

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '27' to each side of the equation.
-27 + 5c + 27 + -6x = 27 + 3x

Reorder the terms:
-27 + 27 + 5c + -6x = 27 + 3x

Combine like terms: -27 + 27 = 0
0 + 5c + -6x = 27 + 3x
5c + -6x = 27 + 3x

Add '6x' to each side of the equation.
5c + -6x + 6x = 27 + 3x + 6x

Combine like terms: -6x + 6x = 0
5c + 0 = 27 + 3x + 6x
5c = 27 + 3x + 6x

Combine like terms: 3x + 6x = 9x
5c = 27 + 9x

Divide each side by '5'.
c = 5.4 + 1.8x

Simplifying
c = 5.4 + 1.8x

See similar equations:

| 2r^2=20r-42 | | 16x+8+10x-10=180 | | 15x+3=-14x+5 | | 3x+6+5x=46 | | 7+3a=-1-5a | | X+5=x-7 | | 14x+6=42 | | -3000x^2+7500=0 | | -2y+5(y-7)=-17 | | X-3i= | | -5m-2=8 | | 10x+15+3x+35=180 | | x-4=12+5x | | 12=9+3x | | X-(6)=-23 | | 96x-1+85x=180 | | 184=3(-7a+8)+a | | 9+-0= | | 106x-1+77x-2=180 | | -62=8(6v+2)-6(v-1) | | 7(u+2)-5u=-2 | | 5(-3)-(-6)= | | 21(x+1)-14(x-1)=21x | | 3(x-24)+3(x-2)=18 | | 2n-6=9+5n | | 10x-10+16x+8=180 | | X=-5+3x | | 8(-4-2r)=5(8-2r) | | X+4=3x-1 | | 3(2x+7)=215 | | 5x^2+2=147 | | 19=1-6x+3x |

Equations solver categories